In situ isobaric lipid mapping by MALDI–ion mobility separation–mass spectrometry imaging. (21st June 2020) - Fu, Tingting; Oetjen, Janina; Chapelle, Manuel; Verdu, Alexandre; Szesny, Matthias; Chaumot, Arnaud; Degli‐Esposti, Davide; Geffard, Olivier; Clément, Yohann; Salvador, Arnaud; Ayciriex, Sophie
Abstract: The highly diverse chemical structures of lipids make their analysis directly from biological tissue sections extremely challenging. Here, we report the in situ mapping and identification of lipids in a freshwater crustacean Gammarus fossarum using matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) in combination with an additional separation dimension using ion mobility spectrometry (IMS). The high‐resolution trapped ion mobility spectrometry (TIMS) allowed efficient separation of isobaric/isomeric lipids showing distinct spatial distributions. The structures of the lipids were further characterized by MS/MS analysis. It is demonstrated that MALDI MSI with mobility separation is a powerful tool for distinguishing and localizing isobaric/isomeric lipids.